The Role of Technological Change in Green Growth - Popp, David (World Bank, Washington, DC, 2013)
By reducing the costs of environmental protection, technological change is important for promoting green growth. This entails both the creation of new technologies and more widespread deployment of existing green technologies. This paper reviews the literature on environmentally friendly technological change, with a focus on lessons relevant to developing countries. It begins with a discussion of the data available for measuring the various steps of technological change. It continues with a discussion of sources of environmental innovation. Given that most innovation is concentrated in a few rich countries, this leads to a discussion of the remaining role for lower-income countries, followed by a discussion of technology transfer. Because of the importance of market failures, the paper discusses the role of both technology policy and environmental policy for promoting environmentally friendly technological change. The review concludes with a discussion of what environmental economists can learn from other fields.